Evaluación fitosanitaria de una plantacion de Aniba rosaeodora Ducke “palo de rosa” establecida en el CIEFOR-UNAP, Loreto, Peru 2023 - Davila Briceño, Alexander Stalin (2024)
This research was carried out in the CIEFOR–UNAP forest plantation, Puerto Almendra, 145 individuals were evaluated over a period of 6 months with the objective of identifying the presence of insects, fungi and other organisms that cause diseases that affect the growth of Aniba rosaeodora Duke. Direct observations were made every 15 days and the presence of different insects that attack plant organs was found, such as: Ruspolia pygmaea “leaf cricket” (13 individuals), Dycladia emorita “tiger moth” (2 individuals), Paranomala undalata “black beetle” (6 individuals), Oreophoetes topoense “stick insect” (1 individual), Paramastak nordistensis “grasshopper cricket” (2 individuals), Xylosandruss compactus “ambrosia beetle” (7 individuals), Planococcus citri “cottony cushion scale” (6 individuals), Euconocephatus thunbergii “pink grasshopper” (1 individual), Omophaita chevrolat “flea beetle” (1 individual); Likewise, two species were found that feed on crickets and exert biological control of the species naturally: Erbessus grossus "red bug" (4 individuals) and Dendropsophus branneri "cricket frog" (1 individual). Shocker-T 90ps insecticide powder was applied every 15 days, dissolving 30g of the insecticide in 20L of water, to eradicate the presence of these insects. The survival rate was determined to be 96.55% (140 live plants), and the mortality rate was 3.45% (5 dead plants). Regarding biometric measurements, the average height was 104.7cm and the diameter was 0.121cm, indicating that the plantation is in the growth process.